2012
DOI: 10.1371/journal.pone.0041584
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of p70S6K in Intestinal Ischemia/Reperfusion Injury in Mice

Abstract: The mTOR signaling pathway plays a crucial role in the regulation of cell growth, proliferation, survival and in directing immune responses. As the intestinal epithelium displays rapid cell growth and differentiation and is an important immune regulatory organ, we hypothesized that mTOR may play an important role in the protection against intestinal ischemia reperfusion (I/R)-induced injury. To better understand the molecular mechanisms by which the mTOR pathway is altered by intestinal I/R, p70S6K, the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 60 publications
4
28
1
Order By: Relevance
“…1A). This is consistent with the report that mTOR is activated in intestinal ischemia-and irradiation-induced intestinal regeneration (37,38). Inhibition of mTORC1 activity by either rapamycin treatment or haploinsufficiency of Rheb in mice resulted in increased apoptosis and decreased cell proliferation, leading to more severe tissue damage in our DSS-or TBNS-induced colitis models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1A). This is consistent with the report that mTOR is activated in intestinal ischemia-and irradiation-induced intestinal regeneration (37,38). Inhibition of mTORC1 activity by either rapamycin treatment or haploinsufficiency of Rheb in mice resulted in increased apoptosis and decreased cell proliferation, leading to more severe tissue damage in our DSS-or TBNS-induced colitis models.…”
Section: Discussionsupporting
confidence: 92%
“…1B), suggesting that S6K1 is probably the key player downstream of mTORC1. Similar results have been reported in intestinal ischemia/ reperfusion injury and LPS-induced lung injury, further supporting our speculation (38,39). Recently, Faller et al (40), using multiple genetically engineered mouse alleles, found that S6K1/2, but not 4EBP1/2, was involved in intestinal regeneration and demonstrated that rapamycin functioned mainly through the mTORC1-S6K pathway rather than through the 4EBP1-eIF4E branch.…”
Section: Discussionsupporting
confidence: 90%
“…Among them, IL-6 locally produced in the intestine has been identified as a key inflammatory cytokine that plays an essential role in damaging the tissue during intestinal I/R. In support of this, it has been demonstrated that 1) both in humans (4) and in mice (5,6), local levels of IL-6 in the intestine are markedly elevated in association with severe tissue damage after intestinal I/R; 2) IL-6 Ϫ/Ϫ mice developed significantly attenuated intestinal damage after I/R; and 3) blocking IL-6 activity in WT mice using anti-IL-6 mAbs greatly retained intestinal tract integrity after I/R (7). Natural IgM has been found to be critical in the pathogenesis of intestinal I/R.…”
mentioning
confidence: 90%
“…The number of positively stained cells in the intestinal mucosa was counted in 50 high-power fields per section under a microscope, as described previously (33).…”
Section: F4/80-positive Cells In Colonic Mucosamentioning
confidence: 99%